2007
DOI: 10.1007/s10719-007-9068-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a tetra- and a trisaccharide related to an anti-tumor saponin “Julibroside J28” from Albizia julibrissin

Abstract: Simple and convergent synthesis of a tetra- and a trisaccharide portions of an antitumor compound Julibroside J(28), isolated from Albizia julibrissin, that showed significant in vitro antitumor activity against HeLa, Bel-7402 and PC-3M-1E8 cancer cell lines is reported. The tetrasaccharide has been synthesized as its p-methoxyphenyl glycoside starting from commercially available D-glucose, L-rhamnose and L-arabinose. The trisaccharide part has been synthesized from commercially available N-acetyl D-glucosamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…The reaction yielded 2,3-di-O-benzoyl, 3-O-benzoyl 24, 2-O-benzoyl and unreacted 23 in a ratio of 1 : 5 : 2 : 1. [25] Finally, chloroacetylation of the 2-OH group using chloroacetic anhydride in CH 2 Cl 2 -pyridine mixture afforded the glucose donor 5 in 90 % yield (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction yielded 2,3-di-O-benzoyl, 3-O-benzoyl 24, 2-O-benzoyl and unreacted 23 in a ratio of 1 : 5 : 2 : 1. [25] Finally, chloroacetylation of the 2-OH group using chloroacetic anhydride in CH 2 Cl 2 -pyridine mixture afforded the glucose donor 5 in 90 % yield (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…We decided to take the 2‐OH inversion approach to introduce the desired β ‐ManNAcA moiety [23] . Thus, in a separate experiment, the known compound 23 [24] was selectively benzoylated at the 3‐OH position using BzCl in CH 2 Cl 2 ‐pyridine [25] at −50 °C. The desired 3‐O‐benzoyl derivative 24 was obtained in 55 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…[10,11] This is primarily due to the acid-labile nature of the p-methoxybenzyl group that results in removal of the group along with the benzylidene and isopropylidene protections. With our experience using H 2 SO 4 -silica [12][13][14][15][16][17][18][19][20][21] as a mild acid source for various carbohydrate transformations, we envisaged that it might provide the adequate acidity for the hydrolysis of the benzylidene and isopropylidene protections without affecting the p-methoxyphenyl group. In fact, we have observed that the isopropylidene protection may be cleaved selectively in the presence of the p-methoxybenzyl group using H 2 SO 4 -silica as an acid source.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the chloroacetate group was selectively cleaved using thiourea 34 to furnish the required disaccharide acceptor 11 in 86% yield. Further glycosylation of the known donor, p-tolyl 2,3,4-tri-O-benzoyl-1-thio-a-D-arabinofuranoside (12) 24 with disaccharide acceptor 11 using NIS in conjunction with H 2 SO 4 -silica afforded the protected trisaccharide 13 in 83% yield. Global deprotection of the trisaccharide was accomplished by treating trisaccharide 13 with 80% AcOH at 80°C followed by NaOMe in MeOH to get the target trisaccharide 2 in 78% overall yield (Scheme 2 1.…”
Section: Introductionmentioning
confidence: 99%